Restoring Impaired Fertility Through Diet: Observations of Switching From High-Fat Diet During Puberty to Normal Diet in Adulthood Among Obese Male Mice - Qi, Xiangyu; Zhang, Meijie; Sun, Mingqi; Luo, Dandan; Guan, Qingbo; Yu, Chunxiao (Frontiers in Endocrinology, 2022)
Background: Obesity is associated with a decrease in testicular function, yet the effects and mechanisms relative to different stages of sexual development remain unclear. The aim of this study is to determine whether high-fat diet-induced obesity impairs male fertility during puberty and in adulthood, and to ascertain its underlying mechanisms. This study aims to further reveal whether restoring to a low-fat diet can improve impaired fertility. Methods: Male mice were divided into 4 groups. The first and second group exposed to a high-fat diet during puberty (HL) and in adulthood (LH). The third and fourth group maintained a continuous high-fat diet (HH) and low-fat diet(LL). Metabolic parameters, fertility parameters, testicular function parameters, TUNEL staining and testicular function-related proteins were evaluated, respectively. Results: The fertility of the mice in the high-fat diet group was impaired, which validated by declines in pregnancy rates and litter weight loss. Further analysis demonstrated the increased number of spermatogenic cell apoptosis and decreased number of sperm and decreased acrosome integrity. The expression of steroidogenic acute regulatory (StAR) and spermatogenesis related proteins (WT-1) decreased. Fertility among the HL group recovered, accompanied by the recovery of metabolism, fertility and testicular function parameters, StAR and WT-1 expression. Conclusions: The findings suggest that high-fat diet-induced obesity impairs male fertility during puberty and in adulthood. The loss of acrosome integrity, the increase of cells apoptosis and the down-regulation of StAR and WT-1 may be the underlying mechanisms. Switching from high-fat diets during puberty to low-fat diets in adulthood can improve male fertility.